Gender Based Teacher Directive Speech Acts in Religious Learning Process at Islamic High School - Mashuda Nur; Agustina (Indonesia Approach Education, 2023)
This research aims to explain the form of directive speech acts used by male teachers and female teachers as well as the differences in Islamic high school. This type of research is qualitative research using descriptive analysis method. The data of this research is the directive speech of male teachers and female teachers. The data collection of this research used the free listening technique. Data validation uses triangulation technique while the data analysis technique is done through three stages, namely the reduction stage, data presentation, and drawing conclusions. There are three findings obtained from this research. First, the speech act that is often used by male teachers is the speech act of ordering while the speech act of begging is rarely used. Second, the speech act most often used by female teachers is the speech act of telling while the rarely used speech acts are begging and advising. Third, the difference is that male teachers use directive speech acts of telling using ordinary imperative sentences, while female teachers use directive speech acts of telling using imperative imperative sentences. The novelty in this research is that there is no previous research that examines the speech acts used by male teachers and female teachers in religious subjects in a madrasa with Mandailing cultural background.